The Effect of A2 Milk on Gastrointestinal Symptoms in Comparison to A1/A2 Milk: A Single-center, Randomized, Double-blind, Cross-over Study - Choi, Yonghoon; Kim, Nayoung; Song, Chin-Hee; Kim, Seulgi; Lee, Dong Ho (Journal of cancer prevention, 2024)
β-Casein, a major protein in cow's milk, is divided into the A1 and A2 type variants. Digestion of A1 β-casein yields the peptide β-casomorphin-7 which could cause gastrointestinal (GI) discomfort but A2 milk containing only A2 β-casein might be more beneficial than A1/A2 (regular) milk. The aim of this study was to evaluate the differences in GI discomfort after ingestion of A2 milk and A1/A2 milk. A randomized, double-blind, cross-over human trial was performed with 40 subjects who experienced GI discomfort following milk consumption. For each intervention period, either A2 milk first (A2→A1/A2) or A1/A2 milk was first consumed for 2 weeks (A1/A2→A2) following a 2-week washout period. GI symptom rating scale (GSRS) scores, questionnaire for digestive symptoms, and laboratory tests including fecal calprotectin were evaluated. For symptom analysis, generalized estimating equations gamma model was used. A2 milk increased bloating ( = 0.041) and loose stools ( = 0.026) compared to A1/A2 milk in GSRS. However, A2 milk caused less abdominal pain ( = 0.050), fecal urgency ( < 0.001) and borborygmus ( = 0.007) compared to A1/A2 milk in questionnaire for digestive symptoms. In addition, fecal calprotectin also decreased or less increased after consumption of A2 milk compared to A1/A2 milk ( = 0.030), and this change was more pronounced in males ( = 0.005) than in females. There were no significant adverse reactions during the trial. A2 milk alleviated digestive discomfort in Koreans following A2 milk consumption (ClinicalTrials.gov NCT06252636 and CRIS KCT0009301).